Muscle typology of youth track-and-field athletes predicts their adult performance: a prospective study - Vandecauter, J.; Van Vossel, K.; Van de Casteele, F.; Derave, W.; Lievens, E. (29th Annual Congress of the European College of Sport Science, 2-5 July 2024, Book of Abstracts, 2024)
INTRODUCTION: Current talent identification programs struggle to successfully identify track-and-field talents at a younger age, mainly because of poor relation between youth and senior performances [1]. Instead, stable biological and performance-related factors, such as muscle fiber type composition (MFTC), may hold promise for more robust predictions. Fast and slow muscle fibers possess distinct characteristics and their ratio is discipline-dependent in elite track-and-field athletes [2]. With the advent of non-invasive techniques, the assessment of MFTC is no longer restricted to muscle biopsies, enabling its use in talented youth [3]. Therefore, the aim of this longitudinal prospective study is to investigate whether MFTC measured at a younger age, is a good predictor for later track-and-field performance. METHODS: Between 2010 and 2019, we included 64 talented youth athletes that were allowed into selective track-and field elite sport schools (age = 15.7 ± 1.3 years, range 12 to 18 years). Their MFTC was non-invasively estimated in the gastrocnemius muscle using 3T proton magnetic resonance spectroscopy of the fast-twitch metabolite carnosine. Youth athletes` MFTC was compared to a discipline-specific elite athlete benchmark population (n = 87, * 1050 IAAF points). A categorical approach was used to assign youth athletes as `match` if their MFTC was within the range (mean ± 1 SD) of the elite athletes for their discipline, otherwise appointed as `mismatch`. The personal best IAAF-score was analyzed as performance parameter, with a follow-up period of 3 to 12 years after the muscle scan. Independent sample t-tests were used with significance set at p * 0.05. RESULTS: The highest IAAF-score was obtained 3.4 ± 2.4 years after the scan. Two-thirds of the athletes were already training for a discipline matching their MFTC, indicating the importance of the coaches` eye. Nevertheless, one-third was still misclassified. The `match` athletes achieved a significantly higher IAAF-score (987 ± 110 vs 915 ± 93 points, p = 0.011) compared to `mismatch` athletes, indicating a better later performance if MFTC at youth level matches with the MFTC of the elite benchmark for their discipline. Of all the matching athletes, 36% achieved an all-time best score above 1050 points, i.e. reaching international standards, compared to only 9% with a mismatching MFTC (p = 0.022). CONCLUSION: This study shows for the first time that youth track-and-field athletes who train for a discipline that is deemed optimal based on their MFTC, perform better at adult age. Therefore, the non-invasive measurement of MFTC can be seen as a new and valuable element in talent identification, identifying the ideal discipline for youth athletes around the age of 15 to 16 years. This is likely expandable to other sports, like cycling, where discipline specialization depends on MFTC.